2012
DOI: 10.1037/a0025887
|View full text |Cite
|
Sign up to set email alerts
|

Using the dual-target cost to explore the nature of search target representations.

Abstract: Eye movements were monitored to examine search efficiency and infer how color is mentally represented to guide search for multiple targets. Observers located a single color target very efficiently by fixating colors similar to the target. However, simultaneous search for 2 colors produced a dual-target cost. In addition, as the similarity between the 2 target colors decreased, search efficiency suffered, resulting in more fixations on colors dissimilar to both target colors, which we describe as a "split-targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
172
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(187 citation statements)
references
References 29 publications
14
172
1
Order By: Relevance
“…The dual-target cost in this experiment might be attributed to complications that arise from having a target defined by two colours. However, another recent study (Stroud, Menneer, Cave, & Donnelly, 2011) has demonstrated a dual-target cost with two targets that are each defined by a single colour, suggesting that the dual-target cost here is not caused by a two-colour target.…”
Section: Discussionmentioning
confidence: 99%
“…The dual-target cost in this experiment might be attributed to complications that arise from having a target defined by two colours. However, another recent study (Stroud, Menneer, Cave, & Donnelly, 2011) has demonstrated a dual-target cost with two targets that are each defined by a single colour, suggesting that the dual-target cost here is not caused by a two-colour target.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that searching for two dissimilar targets, compared to searching for one target, can hinder accuracy, slow responses, and impair attentional guidance (e.g., Menneer, Cave, & Donnelly, 2009;Stroud, Menneer, Cave, & Donnelly, 2012). Security screenings often prohibit more than just two things, which makes this problem even more distressing.…”
Section: The Significancementioning
confidence: 99%
“…The orientation of each target was randomly selected, such that one target was oriented in the horizontal plane (i.e., the gap facing left or right) and the other was oriented in the vertical plane (i.e., the gap facing up or down). The colors were selected from a stimulus set taken from previous studies of dual-target search (Stroud et al, 2012) comprised of 16 colors, with each adjacent color forming equally distant “steps” in color space (see Figure 2). Target colors were randomly selected, with the constraint that they were maximally far apart in color space (i.e., eight “steps”) in order to prevent participants from using combined mental templates of similar colors during search.…”
Section: Methodsmentioning
confidence: 99%
“…To address this question, Stroud, Menneer, Cave and Donnelly (2012) examined eye movements as participants performed single- and dual-target search for items defined by their color. The color difference between the two targets was varied systematically: When the colors were similar to each other (estimated via distance in RGB color space), there was no dual-target cost in performance, relative to single-target baselines.…”
Section: Searching For Multiple Targetsmentioning
confidence: 99%